Evaluating the impact of surface chemistry on adhesion of polymeric systems underwater by means of contact mechanics - Rahmani, Nasim (Kansas State University, 2015)
The overall goal of this study was to assess the effects of surface chemistry on adhesion of polymeric systems underwater. The adhesion is quantified by the thermodynamic work of adhesion (W) when two surfaces are approached and the energy release rate (G) when the surfaces are separated. For some polymeric systems there is a difference between W and G, referred to as adhesion hysteresis. For this study an experimental approach based upon Johnson-Kendall-Roberts (JKR) theory of contact mechanics was utilized to evaluate how surface chemistry affects the adhesion behavior (both W and adhesion hysteresis) in the presence of water. The interfacial interactions were also studied in air and contrasted to those obtained underwater. To accomplish the overall goal of this research, this study was divided into two phases where smooth model surfaces with disparate surface chemistries were used. The model surfaces in the first part included poly(dimethysiloxane) (PDMS), glass surfaces chemically functionalized to display hydrophilic to medium to hydrophobic characteristics, and thin films of wood-based biopolymers. The functionalities used to modify glass surfaces included polyethylene oxide (PEO) with hydrophilic nature; amine, carbomethoxy, and mercapto (thiol) with intermediate characteristics; cyclohexyl, fluorocarbon, and methyl with hydrophobic behavior. In addition to these surfaces, flat PDMS and clean glass surfaces were also used for means of comparison. The wood-derived polymers included two different cellulose types (natural cellulose and regenerated cellulose) as well as one lignin surface (from hardwood milled lignin). These surfaces were probed with native PDMS hemispheres, which are hydrophobic. The results showed that in air the value of W for all model surfaces was independent of the surface chemistry, except fluorocarbon which was lower. Underwater W was significantly affected by the surface hydrophilicity/ hydrophobicity. The adhesion hysteresis both in air and underwater was significantly dependent on the structure of the probed surface. For the second phase PDMS hemispheres were chemically modified with amine functionality to probe model surfaces with hydrophilic and intermediate behavior. These surfaces included glass surfaces functionalized with PEO and amine as well as PDMS sheets that were functionalized with amine. Native PDMS flat surfaces were also used for means of comparison. The results showed that for the selected surfaces both W and hysteresis were affected by the surface chemistry in both media.
Keywords: Adhesion; Underwater; Contact Mechanics; Surface chemistry; Chemistry (0485); Mechanical Engineering (0548)